Simulating the temperature and precipitation signal in an Alpine ice core ... - Brönnimann, Stefan; Mariani, Isabella; Schwikowski, Margit; Auchmann, Renate; Eichler, Anja (ETH Zurich, 2013)
Accumulation and δ18O data from Alpine ice cores provide information on past temperature and precipitation. However, their correlation with seasonal or annual mean temperature and precipitation at nearby sites is often low. This is partly due to the irregular sampling of the atmosphere by the ice core (i.e. ice cores almost only record precipitation events and not dry periods) and the possible incongruity between annual layers and calendar years. Using daily meteorological data from a nearby station and reanalyses, we replicate the ice core from the Grenzgletscher (Switzerland, 4200 m a.s.l.) on a sample-by-sample basis by calculating precipitation-weighted temperature (PWT) over short intervals. Over the last 15 yr of the ice core record, accumulation and δ18O variations can be well reproduced on a sub-seasonal scale. This allows a wiggle-matching approach for defining quasi-annual layers, resulting in high correlations between measured quasi-annual δ18O and PWT. Further back in time, the agreement ... : Climate of the Past, 9 (4) ...